Intervensi Keperawatan Menurunkan Rasa Haus pada Pasien Chronic Kidney Disease (CKD): a Rapid Review - Sandra Pebrianti; Iwan Shalahuddin; Bambang Aditya Nugraha; Theresia Eriyani; Devi Nurrahmawati (Malahayati Nursing Journal, 2023)
ABSTRACT Chronic Kidney Disease (CKD) is one of the increasing health problems. The global prevalence of CKD ranges from 13.4% (11.7-15.1%) of the population, with end-stage kidney replacement around 4.90 - 7.08 million people. To determine effective interventions of thirst management in CKD patients who carried out fluid restriction. The method used is rapid review with article search on four databases, namely, PubMed NCBI, Scopus, ScienceDirect, and Google Scholar. The studies reviewed were empirical studies with quantitative design, and mix-method in English or Indonesian with full text, as well as intervention studies in people with CKD. Based on the results of the analysis conducted, the results of the intervention were obtained namely chewing free sugar gum, sipping ice (ice suction), and gargling with mouthwash. Of the types of interventions found, the highest effectiveness was in the sipping ice intervention (p = 0.000) with a thirst-holding time of ±93 minutes. Thirst management in CKD patients can be done with various interventions, but the principles of fluid restriction must still be observed. Keywords: Chronic Kidney Disease, Interventions, Thirst  ABSTRAK Penyakit ginjal kronis atau Chronic Kidney Disease (CKD) menjadi salah satu masalah kesehatan yang terus meningkat. Prevalensi CKD secara global berkisar di angka 13,4% (11,7-15,1%) penduduk, dengan stadium akhir yang memerlukan penggantian ginjal sekitar 4,90 - 7,08 juta jiwa. Untuk mengetahui intervensi yang efektif manajemen haus pada pasien CKD yang dilakukan pembatasan cairan. Metode yang digunakan adalah rapid review dengan pencarian artikel pada empat basis data yaitu, PubMed NCBI, Scopus, ScienceDirect, dan Google Scholar. Studi yang ditinjau adalah studi empiris dengan desain kuantitatif, dan mix-method dalam bahasa Inggris atau bahasa Indonesia dengan teks lengkap, serta studi intervensi pada penderita CKD. Berdasarkan hasil analisis yang dilakukan, diperoleh hasil intervensi yaitu mengunyah permen karet free sugar, sipping ice (hisap es), dan berkumur dengan mouthwash. Dari jenis intervensi yang ditemukan, efektifitas tertinggi ada pada intervensi sipping ice (p=0,000) dengan waktu menahan haus ±93 menit. Manajemen haus pada pasien CKD dapat dilakukan dengan berbagai intervensi, namun prinsip-prinsip pembatasan cairan yang dilakukan harus tetap diperhatikan Kata Kunci: Chronic Kidney Disease, Intervensi, Rasa Haus